La « théorie des nouvelles professions », une ressource heuristique pour penser la professionnalisation - Emmanuel de Lescure (Éducation et Socialisation)
Centering on the case of the adults trainers, this article wants to show that, even if its echo is much lesser than that of the other works (in particular on school), one of the theoretical elements developed by Bourdieu constitutes even today a heuristics source to think the dynamics of the professional groups and the processes of professionalization. To do it, it suggests considering a point developed in The distinction (1979) around the notion of « new lower middle class ». Mobilizing the results of a secondary analysis of data of the survey Employment of the National institute for statistics and economics studies (INSEE), it examines the social recruitment of adults trainers and the process of segmentation of the occupational group from the 1980s to 2000s to test the current events of what was a posteriori appointed the « theory of the new occupations ».